Electronic Packaging Model with Continuous and Discontinuous Bond Layer - Ting, K.P.; Sujan, Debnath (School of Engineering & Science, Curtin University Sarawak Campus, 2012)
Interfacial stress due to thermal mismatch in layered structure has been considered as one of the major causes of mechanical failure in electronic packaging. The mismatch of the coefficient thermal expansion (CTE) of the materials in multiplayer structure may induce serious stress concentrations to the electronic composites such as interfacial delamitation and die cracking. Therefore, the studies and evaluation of interfacial stress in electronic packaging become significantly important for failure prediction optimum and design of the electronic devices. The thermal mismatch shear stress for hi-layered assembly can be analyzed by using the mathematical models developed by Suhir in 1986. In this research, Finite Element Method (FEM) simulation was performed to a packaging example by using ANSYS. The FEM results were compared to the analytical solutions to determine the validity of the results. The interfacial stresses were further studied with the consideration of continuous and discontinuous bonding in the assembly by analyzing the shear stress growth behavior at the interface of the bonded section. In addition, comparison of shear stress was made between continuous and discontinuous bonded hi-layered assemblies to evaluate their relative effect in electronic packaging. Furthermore, the interfacial stress analysis was carried out on discontinuously bonded Flip Chip Ball Grid Array (FCBGA) which is widely used in current electronic packaging industry. The interfacial stress distribution of FCBGA was analyzed.